Polypharmacy and Drug Use Pattern among Indonesian Elderly Patients Visiting Emergency Unit - Czeresna Heriawan Soejono; Aulia Rizka (Interna Publishing, 2021)
Background: polypharmacy is a major concern for elderly patients, as it links to high morbidity related to drug interaction and adverse drug effects. Not much is known about profile of polypharmacy among elderly subjects visiting emergency department (ED) for acute conditions. Methods: a cross sectional study conducted between July to December 2018 in ED of Cipto Mangunkusumo Hospital Jakarta Indonesia. All elderly patients admitted to ED were included. We evaluated drug use pattern using ATC system along with the association between polypharmacy with sex, age and number of comorbidities. Results: 475 geriatric patients visited EU 247 subjects were male (54.8%; mean age 67.69 (SD 6.58) years old). Polypharmacy was found in 57.6% subjects. The most frequently used of drug was that of alimentary tract and metabolism pharmacologic group, followed by drugs related to blood and blood forming organs, cardiovascular system, and anti-infectives for systemic use. Sex and age were not associated with polypharmacy, while more than 3 comorbidities was associated with polypharmacy. Conclusion: polypharmacy is prevalent among elderly visiting ED in Indonesia, requiring special attention from clinician to evaluate each drug and interaction among the drugs used.